Pendampingan Siswa Siswi Madrasah Ibtidaiyah Khalafiyah Syafi’iyah Zainul Hasan Genggong Terkait Perkembangan Anak dalam Masa Sekolah - Zakyah, Fauzyatuz; Musayyaroh, Hikmatul; Wisudaningsih , Endah Tri (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
This study focuses on mentoring activities for male and female students of Madrasah Ibtidaiyah Khalafiyah Syafi’iyyah Zainul Hasan Genggong related to children’s development during the school period. The main issue identified is the lack of optimal learning motivation and independence among students, which affects their academic achievement and character formation. The purpose of this study is to improve students’ observation skills, creativity, critical thinking, emotional regulation, social interaction, and learning motivation in an integrated manner. This research employed a descriptive qualitative method with observation, interviews, and in-depth documentation as the primary data collection techniques. The findings indicate a significant improvement in students’ concentration, creative expression through drawing, logical thinking, emotional stability, harmonious social interaction, as well as motivation and discipline in learning. The mentoring activities provide a sustainable positive impact on students’ psychological growth and holistic development within the madrasah environment